The Early Predictive Value of Circulating Monocytes and Eosinophils in Coronary DES Restenosis - Li, Shumei; Qiu, Hong; Lin, Zhaorong; Fan, Lin; Guo, Yongzhe; Zhang, Yujie; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2022)
Background Monocytes and eosinophils are involved in intracoronary inflammatory responses, aggravating coronary artery plaque instability and in-stent restenosis (ISR). Aims To investigate an early prediction of ISR in patients undergoing stenting by circulating monocytes and eosinophils. Methods The single-center data of patients undergoing successful drug-eluting stents (DES) implantation from January 1, 2017 to April 30, 2020 were retrospectively analyzed. Of the 4,392 patients assessed, 140 patients with restenosis and 141 patients without restenosis were enrolled. A scheduled postoperative follow-up was proceeded in four sessions: 0–3 months, 3–6 months, 6–12 months, and >12 months. The hematological and biochemical measurement was collected. The angiographic review was completed within two postoperative years. Results Significant associations of monocyte count and percentage with ISR were evident [odds ratio (OR): 1.44, 95% CI: 1.23–1.68, P < 0.001; OR: 1.47, 95%CI: 1.24–1.74, P < 0.001, respectively], which began at 3 months postoperatively and persisted throughout the follow-up period. Eosinophil count and percentage were associated with ISR (OR: 1.22, 95%CI: 1.09–1.36, P = 0.001; OR: 1.23, 95%CI: 1.07–1.40, P = 0.003, respectively), with ISR most significantly associated with the baseline eosinophils. The receiver operating characteristic (ROC) curve analysis showed that the cutoff points of monocyte count and percentage in the ISR prediction were 0.46× 109/L and 7.4%, respectively, and those of eosinophil count and percentage were 0.20 × 109/L and 2.5%, respectively. Conclusion This study, with a long-term follow-up, first provides evidence that the elevated monocytes at three postoperative months and baseline eosinophils may be strong early predictors of ISR after drug-eluting stent implantation. Persistent elevation of monocytes may also be a signal of ISR after percutaneous coronary intervention (PCI).